Pendidikan Gila Gelar? Pemikiran Julian Nida-Rümelin tentang “Kegilaan Akademisasi” (Akademisierungswahn) di Uni Eropa dan Amerika Serikat serta Arti Pentingnya untuk Keadaan Indonesia - Reza A.A Wattimena (WANUA : Jurnal Hubungan Internasional, 2017)
This writing describes several important arguments from Julian Nida-Rümelin concerning academisation madness, which happens in United States and European Union. It shows also the relevance of this argument for Indonesia. This academisation madness can be seen clearly in the obsession of academic title as a result of university education. At the same time, the skilled labor education that is created specifically for certain line of jobs is being forgotten or underestimated. This madness happens, because of the misunderstanding of the society and government concerning the true meaning of education, and how educational policies have direct social, political and economic consequences in reality. Nida-Rümelin provides a deep analysis concerning this matter. He argues also about the importance of government and public wide recognition on the value of skilled education in comparison with academic education. Both have different focus but possess the same philosophical paradigm, namely education as personality development. This article offers also several critical considerations to Nida-Rümelin’s arguments.